La peur du Covid-19 va-t-elle créer de nouveaux hikikomori ? Quel risque pour le vivre ensemble ? Will the Fear of Covid-19 Create New Hikikomori? What is the Risk for Living Together? - Behtane, Abdelkader (Milev Journal of Research and Studies, 2021)
The Covid-19 pandemic has paralyzed the whole world and shattered our relationship with fear. It appears that the one linked to the coronavirus is due to uncertainty and worry, in the sense of deprivation of psychological rest. Indeed, this pandemic has changed our lives as we remained confined in order to avoid contact with the outside as much as possible. Also, we had to learn to survive by applying what we call "barrier gestures". Thus, we wonder if this forced confinement and the fear of contagion could have given rise to the desire to live in reclusion, like the hikikomori. We also wonder about the psychological and societal consequences of this “great confinement”. By dint of living in suspicion and fear, far from each other, isn't there a risk for living together?